2017
DOI: 10.1016/j.gca.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and physical controls on the transformation of amorphous calcium carbonate into crystalline CaCO3 polymorphs

Abstract: Calcite and other crystalline polymorphs of CaCO 3 can form by pathways involving amorphous calcium carbonate (ACC). Previous studies of ACC provide important insights, but apparent inconsistencies in the literature indicate the relationships between ACC composition, local conditions, and the subsequent crystalline polymorphs are not yet established. This experimental study quantifies the control of solution composition on the transformation of ACC into crystalline polymorphs in the presence of magnesium. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
182
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(212 citation statements)
references
References 95 publications
(117 reference statements)
15
182
3
Order By: Relevance
“…The possible effects of ASW compositions on calcium carbonate crystallization [12,[91][92][93] and shell formation in living species [88,90,94] have been investigated in detail. Blue et al [12] studied the transformation of ACC in calcium carbonate solutions, and found that the crystallization pathway, the polymorph selection, and the mineral composition were sensitive to the physical (stir or not) and chemical (Mg/Ca, carbonate/Ca ratio) conditions, which cannot be explained by the classical thermodynamic equilibria of crystallization. This provides a new understanding of biomineralization where organisms might control the physical-chemical factors (such as local alkalinity, pH, and supersaturation) during biomineralization to enable the precipitation of metastable phases with the unusual calcite compositions and textures that cannot be obtained by the classical crystal growth models.…”
Section: Mineralization Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…The possible effects of ASW compositions on calcium carbonate crystallization [12,[91][92][93] and shell formation in living species [88,90,94] have been investigated in detail. Blue et al [12] studied the transformation of ACC in calcium carbonate solutions, and found that the crystallization pathway, the polymorph selection, and the mineral composition were sensitive to the physical (stir or not) and chemical (Mg/Ca, carbonate/Ca ratio) conditions, which cannot be explained by the classical thermodynamic equilibria of crystallization. This provides a new understanding of biomineralization where organisms might control the physical-chemical factors (such as local alkalinity, pH, and supersaturation) during biomineralization to enable the precipitation of metastable phases with the unusual calcite compositions and textures that cannot be obtained by the classical crystal growth models.…”
Section: Mineralization Mediummentioning
confidence: 99%
“…Classical crystallization theories have been widely applied for understanding the crystallization behavior of biomimetic mineralization systems [3,8,9]. However, recent studies have failed to adequately explain many biomimetic crystallization systems using classical crystallization theory [10][11][12], which supposes that crystal nucleation or growth is formed directly from ion-by-ion additions [13]. Recently, researchers began hypothesizing that varied "nonclassical" crystallization pathways were more likely to be a product of biomineralization ( Figure 1) [14], which refers to aggregation-based crystallization [15,16], pre-nucleation clusters [17][18][19][20], and amorphous phase mediated crystallization (APMC) [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Them ain stream in the synthesis of high-Mg calcites is to exploit additives which are either biomolecules extracted from mineral forming organisms [2,[4][5][6] or synthetic compounds rich in carboxylate groups. [23][24][25][26][27] While these studies in aqueous solutions have deepened our understanding of the thermodynamic controls on the phase transformation of calcium carbonate,t he biological relevance of these studies awaits further substantiation because biominerals usually have very unique hierarchical levels of structure formation. [15] Knowing that ACCc ould be stabilized by al arge variety of additives [16,17] and that ion binding can modulate significantly the nucleation events, [18] the functions of the aforementioned additives upon the Mg-calcite formation are at least two folded.…”
mentioning
confidence: 99%
“…TEM images revealed no order in the majority of the detected particles, which was confirmed by the diffuse rings in the selected area electron diffraction patterns but the appearance of nanodomains within the ACC particles (RodriguezBlanco et al, 2008). ACC, which received relatively little attention as one of metastable CaCO3 phases, was increasingly recognized as prevalent during calcification (Blue et al, 2017). ACC may precipitate when the conditions promote high local supersaturations for short periods of time (Blue et al, 2017).…”
Section: Precipitation Of Carbonate Mineral Induced By Virus Lysis Ofmentioning
confidence: 99%
“…ACC, which received relatively little attention as one of metastable CaCO3 phases, was increasingly recognized as prevalent during calcification (Blue et al, 2017). ACC may precipitate when the conditions promote high local supersaturations for short periods of time (Blue et al, 2017). Although the saturation index (SI) of the ACC <0 (Table 2), 25 implying the nonspontaneous ACC formation within the solution, the growth of cyanobacteria in the present experiment created an ACC favorable microenvironment at the 10 th day reflected by the removing of Ca…”
Section: Precipitation Of Carbonate Mineral Induced By Virus Lysis Ofmentioning
confidence: 99%